Mannan oligosaccharides improve the fur quality of raccoon dogs by regulating the gut microbiota - Yuan, Chongshan; Ren, Lili; Sun, Rui; Yun, Xianghong; Zang, Xiao; Zhang, Aiwu; Wu, Min (Frontiers in Microbiology, 2023)
Adding antibiotics to animal basal diets can improve growth and production performance. However, the use of antibiotics poses a potential threat to public health safety. The study was conducted to investigate the effects of different levels of mannan oligosaccharides (MOS) on the fur quality, nutrient apparent digestibility, serum immunity, antioxidant status, intestinal morphology, and gut microbiota of fur-growing raccoon dogs. Divide 24 male raccoon dogs (120 ± 5 d) of similar weight (5.01 ± 0.52 kg) into 4 groups randomly. Add 0, 0.05, 0.1, and 0.2 % MOS to the basal diets of groups C, L, M, and H, respectively. Compared to the C group, the addition of 0.05 % and 0.1 % MOS in the diet increased the apparent digestibility of crude protein (CP), Underfur length (UL), Guard hair length (GL), immunoglobulin A (IgA), immunoglobulin G (IgG), and immunoglobulin M (IgM) levels in the serum (P < 0.05); Under the dosage of 0.05 % MOS, the activities of Superoxide Dismutase (SOD) and catalase (CAT) increased (P < 0.05). Compared to the C group, adding 0.05 % MOS significantly increased the VH/CD of the duodenum and ileum, while also increasing the VH and CD of the jejunum (P < 0.05). Through Spearman correlation analysis of the gut microbiota, it was found that MOS can improve fur quality by reducing the abundance of Dorea while improving the immune response of raccoon dogs by reducing the abundance of Blautia and Gemmiger. In conclusion, MOS can improve the fur quality, serum immunity, antioxidant capacity, and gut microbiota of raccoon dogs. Therefore, MOS has the potential to replace antibiotics.